A congested match schedule alters internal match load and affects salivary immunoglobulin A concentration in youth soccer players - Mortatti, A. L.; de Oliveira, R. S. C.; de Lima Pinto, J. C. B.; Galvão-Coelho, N. L.; de Almeida, R. N.; Aoki, M. S.; Moreira, A. (The Journal of Strength and Conditioning Research, 2022)
The aim of this study was to analyze the effects of a congested match schedule (CMS) undertaken after a tapering week, on internal match load (IML) and salivary immunoglobulin A (SIgA) concentration in 12 youth soccer players (16.6 ± 0.5 years; 175 ± 8 cm; 65 ± 8 kg) who performed 4 official matches within a 4-day period. Internal match load was determined using the session-rating of perceived exertion method and the competitive strain (CS) and monotony index (MI) were also determined. Saliva sampling was conducted, before the last training day of a tapering week (training) preceding the CMS, 60 minutes before the first match (match-1), and 22 hours after match 4 (postmatch 4). Salivary immunoglobulin A was analyzed by ELISA. The results of the analysis of variance with repeated measures showed a significant difference for IML across the matches (p < 0.001). A significant reduction in SIgA was observed from prematch 1 to postmatch 4 (p = 0.019). Regarding the change in SIgA (Delta SIgA), 58.3% of the players presented values equal/higher than the minimal detectable change. A large within-individual correlation was observed between Delta SIgA and MI and CS (r = 0.71 and r = 0.72: p < 0.01, respectively). The current findings suggest that youth players participating in a CMS may present a decrease in mucosal immunity function. In addition, data suggest that the MI and CS may be used as valuable markers for monitoring competition load during CMS in youth soccer players.